2019
DOI: 10.48550/arxiv.1903.04157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distributed Randomized Gradient-Free Mirror Descent Algorithm for Constrained Optimization

Abstract: This paper is concerned with multi-agent optimization problem. A distributed randomized gradient-free mirror descent (DRGFMD) method is developed by introducing a randomized gradient-free oracle in the mirror descent scheme where the non-Euclidean Bregman divergence is used. The classical gradient descent method is generalized without using subgradient information of objective functions. The proposed algorithm is the first distributed non-Euclidean zeroth-order method which achieves an O( 1 √ T ) convergence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Aforementioned ZO optimization algorithms are all centralized and thus not suitable to solve distributed optimization problems. Recently distributed ZO algorithms have being proposed, e.g., distributed ZO gradient descent algorithms [53]- [57], distributed ZO push-sum algorithm [58], distributed ZO mirror descent algorithm [59], distributed ZO gradient tracking algorithm [57], distributed ZO primal-dual algorithms [60], [61], distributed ZO sliding algorithm [62].…”
Section: A Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Aforementioned ZO optimization algorithms are all centralized and thus not suitable to solve distributed optimization problems. Recently distributed ZO algorithms have being proposed, e.g., distributed ZO gradient descent algorithms [53]- [57], distributed ZO push-sum algorithm [58], distributed ZO mirror descent algorithm [59], distributed ZO gradient tracking algorithm [57], distributed ZO primal-dual algorithms [60], [61], distributed ZO sliding algorithm [62].…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Among these algorithms, the algorithms in [53], [54], [57]- [59], [61] are suitable to solve the deterministic form of (1), while the algorithm in [60] can be directly applied to solve the stochastic optimization problem (1). However, the algorithm in [60] requires each agent to have an O(T ) sampling size per iteration, which is not favorable in practice, although it was shown that first-order stationary points can be found at an O(p 2 n/T ) convergence rate.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Previous Work For both deterministic and stochastic scenarios of problem (1), a large body of literature is devoted to first-order gradient based methods with a consensus scheme (see the papers cited above and references therein). On the other hand, the study of zero-order methods was started only recently [27,29,28,11,37,35]. The works [27,37,35] are dealing with zero-order distributed methods in noise-free settings while the noisy setting is developed in [11,29,28].…”
Section: Introductionmentioning
confidence: 99%
“…[13] focus on applying the push-sum technique in distributed ZO optimization in order to handle direct communication between agents. [14] provided distributed ZO mirror descent algorithm. [15] utilized the gradient tracking technique in distributed ZO optimization problems.…”
Section: Introductionmentioning
confidence: 99%